2017
DOI: 10.14800/rci.1572
|View full text |Cite
|
Sign up to set email alerts
|

Targeting sympathetic glia for treating cardiovascular diseases

Abstract: Gq G protein-coupled receptor (Gq-GPCR) signaling in glial fibrillary acidic protein-expressing (GFAP + ) glia is essential for neuron-glia interaction in the Central Nervous System (CNS). However, the exploration of the roles of Gq-GPCR signaling in peripheral GFAP + glia has just begun. Our recent study showed that GFAP + glia in the sympathetic ganglia, namely satellite glial cells (SGCs), positively modulate sympathetic-regulated cardiac functions following their Gq-GPCR activation. In this research highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Therefore, Gi-DREADD has been commonly used to inhibit neuronal activity and decrease signal transduction in neural circuits [ 78 ]. Gi-DREADD can be expressed transgenically [ 21 ] or with the help of viral vectors [ 79 ]. In this study, we demonstrated high tropism of Gi-DREADD expression in TRPV1-positive neurons in lumbosacral DRG, and in the dorsal horn of the spinal cord using TRPV1-Cre mice and hSyn promotors in AAV vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Gi-DREADD has been commonly used to inhibit neuronal activity and decrease signal transduction in neural circuits [ 78 ]. Gi-DREADD can be expressed transgenically [ 21 ] or with the help of viral vectors [ 79 ]. In this study, we demonstrated high tropism of Gi-DREADD expression in TRPV1-positive neurons in lumbosacral DRG, and in the dorsal horn of the spinal cord using TRPV1-Cre mice and hSyn promotors in AAV vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Gi-DREADD has been commonly used to inhibit neuronal activity and decrease signal transduction in neural circuits [78]. Gi-DREADD can be expressed transgenically [21] or with the help of viral vectors [79].…”
Section: Manipulation Of Sensory Neuronal Signaling To Improve Bladder Sensitivitymentioning
confidence: 99%